Problems of the Islamic world of present-day Ukraine - T. Hazyr-Ogly (Українське Pелігієзнавство, 2008)
Modern Ukraine belongs to a group of European countries that have their own indigenous Muslim population. Islam has more than a thousand years of history in Ukraine. But for a long time, the Muslim religion existed in the Ukrainian territory illegally, which caused its decline.